The influence of geometry and reference distance on resection accuracy: An analysis of student surveying calculations - Elisa Maiyenti; Khairul Hamdi; Annisa Irena Rahmatita; Johan Ariyantoni; Fani Keprila Prima (Jurnal Pendidikan Teknologi Kejuruan, 2026)
This study investigates how geometric configuration and reference-point distance affect the accuracy of resection in student surveying calculations, using RTK GNSS coordinates as the reference benchmark. Although resection remains a fundamental method in surveying education and practice, its accuracy is highly sensitive to network geometry and field setup quality, while empirical evidence from student calculation contexts remains limited. To address this gap, the study employed an empirical accuracy-assessment design based on campus field-practicum data generated by student teams using total station observations and RTK GNSS control coordinates. The analysis compared resection-derived and RTK-based coordinates through component-wise discrepancies and horizontal positional error and then interpreted the results in relation to the geometric properties of each resection configuration. The findings show that most observed configurations produced relatively small horizontal errors, indicating that resection can yield acceptable station coordinates in educational field settings. However, accuracy varied considerably across cases. Configurations characterized by balanced point distribution, moderate station angles, and proportionate reference-point distances generally produced more reliable results, whereas stretched or near-collinear configurations were associated with weaker accuracy. At the same time, the results indicate that favorable geometry alone does not guarantee strong performance, because observational execution also remains influential. The study contributes to surveying education by reframing resection as an empirical accuracy problem shaped by both geometric design and field practice.